REFORMULASI KEBIJAKAN HUKUM PIDANA TERHADAP PENGAWALAN AMBULANS OLEH KOMUNITAS PENGAWAL AMBULANS DI INDONESIA - Johannes Jum Joghi Pangaribuan; Maria Maya Lestari; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Priority vehicles as regulated in article 134 of the Road Traffic and Transportation Law must beescorted by the authorized party, namely the police. However, in practice it is very rare to find anambulance escort by the police. This then gave birth to a sense of community concern to form anambulance guard community in Indonesia. However, this reaps the pros and cons in society and alsocontradicts the positive law in force in Indonesia. The purpose of writing this thesis, namely: First, to findout the urgency of forming an ambulance escort community. Second, to find out the arrangements forescorting ambulances in Indonesian criminal law. Third, to find out the reformulation of criminal lawpolicies against ambulance escorts in the future.This research is classified into this type of research which is normative legal research or can alsobe called doctrinal legal research. Normative legal research is library law research. In this normativeresearch the authors conducted research on legal principles. Research on legal principles, namelyresearch conducted on legal principles which are benchmarks for behaving or behaving appropriately orinappropriately. This research is descriptive analysis in nature, namely describing and analyzing theproblems raised which aim to describe concretely the reformulation of criminal law policies againstambulance escorts by the ambulance escort community in Indonesia.From the results of the research and discussion it can be concluded that, first, the ambulance escortcommunity was born in the midst of anxiety and empathy from community groups who care about priorityvehicles in emergencies such as fire engines and ambulances that are stuck in a traffic jam without anyescort; secondly, in the current Indonesian criminal law, it is stipulated that only the police, in this casethe traffic police, have the right to escort priority vehicles including fire engines and ambulances; third,there needs to be an effort to reformulate or renew criminal law, namely creating a codification ofcriminal law to further regulate the escort of ambulance vehicles by the community and create legalcertainty.Keywords: Reformulation-Criminal Law Policy-Ambulance Escort